ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТҮРЛЕРИНДЕ ҲӘМЛЕДАР АНАЛАРДЫҢ ДЕНСАЎЛЫҒЫН САҚЛАЎ ҲӘМ БӨБЕККЕ КҮТИМ ЖАСАЎ ТӘЖИРИЙБЕЛЕРИ - Қурбанбаева, А.Ж. (ILIM hám JÁMIYET, 2021)
The article tells about how the inhabitants of Karakalpakstan since ancient times took care of pregnant women and babies, about the traditions of the people and treating the inhabitants of Karakalpakstan, about the methods of feeding the baby.